The astronomical and calendrical calculations in the 6th Hymn de Crucifixione by Ephrem the Syrian in the old Babylonian, Jewish and Christian context - Sofia Fomicheva (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ III. Filologiâ)
the paper is focused on the astronomical and calendrical lore which the Syriac poet-theologian Ephrem the Syrian abundantly uses in his 6th hymn De crucifixione. In this hymn devoted to the interpretation of three days problem of Jesus’ resurrection, the Syriac poet and theologian employs some astronomical data, i.e., the duration of solar and lunar years, the duration of the lunar months, the necessity of the intercalations in the calendars etc. The author analyses this lore in the context of the astronomical knowledge existing to Ephrem’s epoch. On the one hand, the article pays attention to the similar use of the astronomical data in a lot of Jewish and Christian works of the 3rd and 4rd centuries. In this period the astronomical calculations have been used actively both in Christian and Jewish milieux. On the other hand, the calculations by Ephrem mirror the peculiarities of the region of the north Mesopotamia where he lived and created his works. For example, the author demonstrates that Ephrem could be influenced by the old Babylonian astronomical theory and use in his computations the Babylonian “double hour”. In the article is also demonstrated that the calculations by Ephrem are striking similar to the ones in the “Panarion” by Epiphanius of Salamis. Epiphanius seems to be acquainted with Ephrem’s works or to use the similar tradition stretching back to the Babylonian one. The author draws a conclusion that the calculations in the hymns are used to express Ephrem’s self-presentation as the scribe and the sage who obtains the cosmic “secrets”. This picture is deep rooted as in the old Mesopotamian literature as in Jewish Aramaic writings. The author points out that Ephrem uses the astronomical lore in the liturgical context and not in the theological “scientific’’ tractate. Hence, Ephrem constructs a new religious and poetic “myth” about the Crucifixion and feast of Pascha upon the astronomical dimensions it has both in the Christian and in the Jewish traditions.